Odpowiedzi

2010-01-08T20:22:56+01:00
10x-5y=8x+4
3x+1=y+7
10x-8x-5y=4
3x-y=7-1
2x-5y=4/*(-1,5)
3x-y=6
-3x+7,5y=-6
3x-y=6
6,5y=0
y=0
3x+1=0+7
3x=7-1
3x=6
x=2
2010-01-08T20:25:43+01:00
5(2x-y)=8x+4
3x+1=y+7

10x-5y=8x+4
3x-y=7-1

10x-8x-5y=4
3x-y=6

2x-5y=4
3x-y=6

-y=6-3x / * ( -1)
2x5y=4

y=-6+3x
2x+5(-6+3x)=4

y=-6+3x
2x-30+15x=4

y=-6+3x
17x=34 / ÷17

y=-6+3x
x=2

y=-6+3 * 2
x=2

y=0
x=2

;)
2010-01-08T20:31:35+01:00
5(2x-y)=8x-4
3x+1y+7

10x-5y=8x-4
3x+1=y+7

10x-5y-8x=-4
3x-y=6

2x-5y=-4/*(-3)
3x-y=6/*2

-6x+15y=12
6x-2y=12

13y=24

y=24/13=1 i 11/13
3x-1 11/13=6

3x=102

x=34
y=1 11/13